Answer:
(x, y ) → (x + 11, y - 11 )
Step-by-step explanation:
Consider the point U and its image U'
U (- 9, 1 ) → U' (2, - 10 )
This represents a shift of 2 - (- 9) = 2 + 9 = + 11 → in the x- direction and
- 10 - 1 = - 11 ↓ in the y- direction
This can be shown in the translation rule
(x, y ) → (x + 11, y - 11 )
Answer:
63
Step-by-step explanation:
score 75 is one standard dev below the mean ====>to the mean encompasses approx 34% of scores
.34 * 186 = 63
12-3.7+(1/3)=constant
259/30=constant
The answer would be ~-196xy^5~
Hope this helps
Have a great day/night
![q=\frac{h^{2}-k^{2}}{3m}](https://tex.z-dn.net/?f=q%3D%5Cfrac%7Bh%5E%7B2%7D-k%5E%7B2%7D%7D%7B3m%7D)
Cross-multiplying and rearranging, we get:
![k^{2}=h^{2}-3mq](https://tex.z-dn.net/?f=k%5E%7B2%7D%3Dh%5E%7B2%7D-3mq)
or written without using latex:
k^2 = h^2 - 3mq
Can you finish now?